From Emotion to Intention: Mapping the Evolution of Brand Love Research Through a Systematic Literature Review - Marselinus; Syah, Tantri Yanuar Rahmat; Kustiawan, Unggul; Sofia, Regina Deka (Ilomata International Journal of Management, 2026)
This study aims to identify, analyze, and systematically synthesize the intellectual and empirical development of brand love research from 2016 to 2024. The novelty of this review lies in its integrative approach that not only maps how the construct has evolved conceptually and methodologically across 43 Scopus-indexed journal articles, but also distinguishes itself from previous reviews by combining a PRISMA-guided screening procedure with bibliometric visualization to uncover deeper thematic structures. Using PRISMA as the primary protocol, the article selection process was carried out transparently and stepwise, complemented by bibliometric analyses in VOSviewer that reveal emerging clusters and patterns of scholarly interconnections. The findings indicate that brand experience, brand trust, and customer engagement consistently function as dominant antecedents and outcomes within brand love research. Recent studies also emphasize the growing role of digital platforms and emotional authenticity in shaping stronger consumer–brand relationships. Overall, this review clarifies the theoretical progression of brand love from emotional attachment toward behavioral intention and offers an enhanced research agenda that advances cross-cultural and digital marketing perspectives.